Cytological Diagnosis of Ovarian Tumors - Ahmed Al Qteishat (Journal of Global Pharma Technology, 2020)
Ovarian cancer is one of the most common oncology disorders of the female reproductive system. The aim of the study is to estimate the efficiency of cytological methods in identification of specific characteristics of ovarian cancer and other cancers of female reproductive system. The research was conducted in oncology clinics of Moscow (Russian Federation) and Sofia (Bulgaria) within a period between 2012 and 2019. The study involved 373 cancer female patients who were divided into two groups: the study group (242 women, average age 38.5 ± 7.8 years) and the comparison group (131 women, average age 42.1 ± 9.0 years). The study group included patients diagnosed with ovarian, breast, and endometrial cancer, while the comparison group comprised patients with stomach and lung cancer. The methods of light microscopy, immunocytochemistry and cytological methods were applied in this research. Two types of breast cancer (with ductal breast cancer predomination over the lobular one) and three types of ovarian cancer were specified. The final diagnosis of small cell lung cancer was 15% of lung cancer cases. This cytocentrifuge method was applied in 20% of ovarian cancer cases. Immunocytochemistry revealed a significant response to epithelial antibodies and a negative response to mesothelial ones in breast cancer (p ≤ 0.001). Also, there was no response to monoclonal antigens in ovarian cancer (p ≤ 0.001). This enabled the researchers to recognize and diagnose the mentioned cancer types. A one-year mortality of breast and ovarian cancer was established in 45-47% of patients, which indicated that disease was diagnosed at advanced stages. The study showed the cytological methods to be not equally used in different cancer types: mostly used in breast and ovarian cancers of the study group and almost not applied in lung cancer. In the comparison group, such results were obtained only in stomach cancer. Cell vacuolization was detected in 65% of ovarian cancer cases, while in 80% of ductal breast cancer cases there were specified clusters of spherical cells. Cell structures in the form of bands and chains were found in 75% of lobular breast cancer cases. Single signet ring cells were identified in 20% of stomach cancer cases in the comparison group. The results of the study proved the cytological methods to be significantly important in facilitating the diagnosis of adenogenous ovarian and breast cancer in the study group. Keywords: Ovarian cancer, Breast cancer, Endometrium, cytological methods, Monoclonal antigens.